(untitled) (Global Journal of Human-Social Science, 2023)
The main aim of this research is to determine how to develop sustainable development for the Munda community based on their current socio-economic structure in view of their current condition. The study is mainly quantitative in nature. Koira and Dumuria upazilas of Khulna district and Shyamnagar, Debhata, and Tala upazilas of Satkhira district were selected through convenient sampling techniques for the purpose of collecting primary data because a large part of the Munda community lives in these areas. A structured questionnaire was used to collect data from 250 respondents from five preselected areas. The respondents were selected using a simple random sampling technique. The data was analyzed in terms of statistical indicators of frequency and percentage. The results of the study show that social indicators, economic indicators, and cultural factors are very weak among the Munda community. Among the social indicators, Munda women and men have very little interest in following hygiene rules (sanitation, birth control).